Implementation of Cardovascular Cell Therapy Network trials: challenges, innovation and lessons learned from experience in the CCTRN. (November 2013) - Park, Ki E; Moyé, Lemuel A; Henry, Timothy D; Perin, Emerson C; Sayre, Shelly L; Bettencourt, Judy; Vojvodic, Rachel W; Olson, Rachel E; Pepine, Carl J
The cardiovascular cell therapy network was developed by the National Heart, Lung and Blood Institute to design and conduct clinical trials to advance the field of cardiovascular (CV) cell-based therapy. The Cardiovascular Cell Therapy Network successfully completed three clinical trials involving approximately 300 subjects across five centers and six satellites. Although the concept of a network within clinical trials research is not new, the knowledge gained in the implementation of such large-scale trials, particularly in novel therapeutic areas such as cell therapy is not often detailed in the literature. The purpose of this communication is to summarize key factors in achieving network goals and share the knowledge gained to promote success in future cardiovascular disease cell therapy trials and networks.